Cost and Performance Analysis of Logistics on E-Commerce Platforms: A Management Accounting Approach to Industrial Operational Efficiency - Faisal Rizal Zainal; Rahmawati R; Nurdjanna Fadjrin Uluputty; Eka Novianti Irna Bata Ilyas; Nur Vadila Putri (Manunggal Halim Jaya, 2026)
This study examines logistics cost structures and logistics performance on e-commerce platforms from a management accounting perspective to understand their implications for industrial operational efficiency. Using a qualitative literature-based research approach, the study systematically reviews recent peer-reviewed publications in the fields of e-commerce logistics, supply chain management, and management accounting, and synthesizes them through thematic analysis. The findings indicate that logistics costs in e-commerce environments are predominantly activity-driven, highly variable, and concentrated in warehousing, last-mile delivery, and reverse logistics, where service-level requirements strongly influence cost behavior. The analysis further reveals that logistics performance indicators—particularly delivery reliability, fulfillment accuracy, and return processing efficiency—play a critical role in converting cost management efforts into operational efficiency outcomes. Moreover, the study highlights that management accounting systems integrating activity-based costing and multidimensional performance measurement provide superior cost visibility and support strategic decision-making in complex logistics networks. Overall, the research contributes to the literature by conceptualizing industrial operational efficiency as the result of effective alignment between logistics cost management and performance measurement, rather than cost minimization alone, and offers insights relevant to both academic inquiry and managerial practice in digital commerce environments.